2015
DOI: 10.33549/physiolres.932977
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Soluble Epoxide Hydrolase Does Not Improve the Course of Congestive Heart Failure and the Development of Renal Dysfunction in Rats With Volume Overload Induced by Aorto-Caval Fistula

Abstract: The detailed mechanisms determining the course of congestive heart failure (CHF) and associated renal dysfunction remain unclear. In a volume overload model of CHF induced by creation of aorto-caval fistula (ACF) in Hannover Sprague-Dawley (HanSD) rats we explored the putative pathogenetic contribution of epoxyeicosatrienoic acids (EETs), active products of CYP-450 dependent epoxygenase pathway of arachidonic acid metabolism, and compared it with the role of the renin-angiotensin system (RAS). Chronic treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 48 publications
(48 reference statements)
5
41
0
Order By: Relevance
“…The reason for such presentation is that, not surprisingly, the animals that died in connection with ACF-induced CHF, in the week preceding the death showed the highest CHF score. This relationship was demonstrated in our original studies in which this scoring system was developed 31,48 and the result was that after the first death a paradoxical improvement of CHF score was observed in contrast to a decrease in survival rate. As shown in Fig.…”
Section: Series1:evaluationofsex-linked Differencesinthecourseofacfmentioning
confidence: 82%
See 1 more Smart Citation
“…The reason for such presentation is that, not surprisingly, the animals that died in connection with ACF-induced CHF, in the week preceding the death showed the highest CHF score. This relationship was demonstrated in our original studies in which this scoring system was developed 31,48 and the result was that after the first death a paradoxical improvement of CHF score was observed in contrast to a decrease in survival rate. As shown in Fig.…”
Section: Series1:evaluationofsex-linked Differencesinthecourseofacfmentioning
confidence: 82%
“…Rats were anaesthetized (tiletamine + zolazepam 8 mg/kg; Virbac SA, Carros, France; and xylasine 4 mg/kg; Spofa, Czech Republic, intramuscularly) and CHF was induced by volume overload from ACF created using needle technique as originally described by Garcia and Diebold 62 and employed and validated by many investigators including our own group. 20,21,[29][30][31][32][33][34][35][36]48 Briefly, after exposure of the abdominal aorta and inferior vena cava between the renal arteries and iliac bifurcation, the aorta was temporarily occluded at this segment for about 40 seconds. An 18-gauge needle (diameter 1.2 mm) was inserted into the abdominal aorta and advanced across its wall into the inferior vena cava to create ACF.…”
Section: Chfandckdmodelsandgonadectomymentioning
confidence: 99%
“…Remarkably, chronic treatment with ACEi considerably improved the survival rate and inhibited the development of renal dysfunction in ACF HanSD rats. 37 The recognition of the different effects of sEH inhibition on the course of CHF in TGR and HanSD rats underscores the importance of the interaction of hypertension, RAS and CYP-derived metabolites in the progression of CHF-related mortality and development of renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Male rats at the initial age of 9 weeks were anesthetized (tiletamine + zolazepam, Virbac SA, Carros Cedex, France, 8 mg/kg; and xylasine, Spofa, Czech Republic, 4 mg/kg intramuscularly) and CHF was induced by volume overload induced by creation of ACF using a needle technique as originally described by Garcia and Diebold (1990) and validated by many investigators including our own group (Abasi et al 2011, Benes et al 2011, Brower et al 1996, Červenka et al 2015a, Červenka et al 2015b, Melenovsky et al 2012. Briefly, after exposure of the abdominal aorta and inferior vena cava between the origin of the renal arteries and iliac bifurcation, the aorta was temporarily occluded for about 40 sec.…”
Section: Chf Modelmentioning
confidence: 99%
“…The rat with aorto-caval fistula (ACF) presents a well-defined model of CHF due to volume overload. It is characterized by cardiac remodeling, congestion, and marked activation of the intrarenal RAS with impairment of renal function; the model has many features similar to untreated human CHF and is recommended by American Heart Association (Abasi et al 2011, Benes et al 2011, Červenka et al 2015a, Houser et al 2012, Melenovsky et al 2012. The Ren-2 transgenic rat model (TGR) combines endogenous activation of the RAS and hypertension (Jacinto et al 1999, Kopkan et al 2005, Kujal et al 2014, Mullins et al 1990, Neckář et al 2012 and we found recently that both TGR and normotensive Hannover Sprague-Dawley (HanSD) rats (transgenenegative control to TGR) with ACF-induced CHF exhibited tissue EETs deficiency that could be corrected by chronic sEH inhibition (Červenka et al 2015a, Červenka et al 2015b).…”
Section: Introductionmentioning
confidence: 99%